Pengembangan Panduan Teknik Sosiodrama Daring untuk Meningkatkan Kecerdasan Emosi Siswa Kelas X SMA - Abda’u Bagas Tino; Diniy Hidayatur Rahman; Yuliati Hotifah; Abda’u Bagas Tino; Diniy Hidayatur Rahman (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: This research and development aims to produce an online sociodrama guidebook product to improve emotional inteliigence. This research and development method uses research and development from Borg and Gall using six procedures. The results of this study show : (1) material expert test obtained an average score of 3,71 and 3,57 with an inter-rater reliability score of 0,64 (2) media expert test obtained an average score of 3,82 and 3,91 with an inter-rater reliability score of 0,73 (3) the test of prospective users of the product obtained an average score of 3,92. This shows that the online sociodrama guidebook to improve the emotional intelligence of high school students has high acceptance and is very feasible to use. This guidebook is expected to be an attractive alternative media for guidance services and is easy to apply by counselors, especially in improving emotional intelligence. Abstrak: Penelitian pengembangan ini bertujuan menghasilkan produk buku panduan sosiodrama daring untuk meningkatkan kecerdasan emosi. Metode penelitian dan pengembangan ini menggunakan Research and Development dari Borg dan Gall dengan memakai enam prosedur. Hasil dari penelitian ini bahwa : (1) uji materi memperoleh skor rerata 3,71 dan 3,57 dan skor reliabilitas antar rater 0,64 (2) uji ahli media diperoleh rata-rata 3,82 dan 3,91 dengan skor reliabilitas antar rater 0,73 (3) uji calon pengguna produk diperoleh rata-rata 3,92. Hal ini menunjukkan buku panduan sosiodrama daring untuk meningkatkan kecerdasan emosi siswa SMA memiliki keberterimaan yang tinggi dan sangat layak digunakan. Buku panduan ini diharapkan menjadi alternatif media layanan bimbingan yang menarik dan mudah diterapkan oleh konselor khususnya dalam meningkatkan kecerdasan emosi.